2021
DOI: 10.1108/ijchm-03-2021-0300
|View full text |Cite
|
Sign up to set email alerts
|

Beauty premium or beauty penalty in sharing accommodation situations based on lay theories

Abstract: Purpose Limited research has paid attention to the physical attractiveness stereotype in peer-to-peer sharing accommodation settings. Since the high-risk situations in sharing accommodations, this paper aims to exam whether beauty premium is still relevant in peer-to-peer (P2P) accommodation. Design/methodology/approach The mixed method, including 2,506 secondary data analysis and two scenario experiments, is carried out to test the research framework. Findings The results show that both beauty premium and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 76 publications
0
9
2
1
Order By: Relevance
“…Our study further verified the roles of hosts' facial attractiveness on consumers' booking intentions and willingness to pay. Moreover, different from previous studies demonstrating either a positive U-shaped (Peng et al, 2020) or an inverted U-shaped relationship (Li et al, 2022) between hosts' facial attractiveness and consumer behavior, we found that the impacts of hosts' facial attractiveness were linear.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our study further verified the roles of hosts' facial attractiveness on consumers' booking intentions and willingness to pay. Moreover, different from previous studies demonstrating either a positive U-shaped (Peng et al, 2020) or an inverted U-shaped relationship (Li et al, 2022) between hosts' facial attractiveness and consumer behavior, we found that the impacts of hosts' facial attractiveness were linear.…”
Section: Discussioncontrasting
confidence: 99%
“…Also distinct from some studies (Barnes, 2021;Li et al, 2022) discussing the effect of facial attractiveness through the mechanism of perceived trustworthiness, this study unearthed the underlying mechanism of the beauty premium on mental imagery theory. Results highlighted the mediating roles of perceived enjoyment (i.e., a positive emotional state when the behavioral inhibition system is activated) and perceived threat (i.e., a negative emotional state when the behavioral activation system is activated), which shaped consumers' booking intentions and willingness to pay.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations